2013
DOI: 10.1007/s00284-013-0464-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Analysis Calls for a Reappraisal of the Red Rain Cells of Kerala

Abstract: Early studies on the coloured particles that fell as red rain over southern India identified them as unicellular eukaryotes such as members of the red algae or fungi; however, the results of the present investigation are not consistent with this designation. Using transmission electron microscopy, we have demonstrated significant differences in the ultrastructure when compared with representative species from these other groups. Most notably, the red rain cells show no evidence of typical eukaryotic internal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Using transmission electron microscopy, Gangappa et al [33] demonstrated significant differences in the ultra-structure of red cells when compared with representative species from these groups. The red rain cells showed no evidence of typical eukaryotic internal structures such as mitochondria or endoplasmic reticulum.…”
Section: Evidences For Unusual Nature and Extraterrestrial Origin Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Using transmission electron microscopy, Gangappa et al [33] demonstrated significant differences in the ultra-structure of red cells when compared with representative species from these groups. The red rain cells showed no evidence of typical eukaryotic internal structures such as mitochondria or endoplasmic reticulum.…”
Section: Evidences For Unusual Nature and Extraterrestrial Origin Of mentioning
confidence: 99%
“…The red rain cells showed no evidence of typical eukaryotic internal structures such as mitochondria or endoplasmic reticulum. Also comparisons based on elemental composition using energy-dispersive X-ray analysis, as well as Raman spectral signatures demonstrate significant dissimilarities in their molecular composition and concluded that the identity and origins of the red rain cells remain an enigma [33].…”
Section: Evidences For Unusual Nature and Extraterrestrial Origin Of mentioning
confidence: 99%